Partial Kluver-Bucy syndrome secondary to tubercular meningitis - Jha, Kunal Kishor (BMJ Case Rep, 2016)
Tubercular meningitis (TBM) is a devastating extra pulmonary manifestation of tuberculosis and demonstrates a high neurological morbidity. A rare complication of this condition is Kluver-Bucy syndrome (KBS), which is a neurobehavioral disorder characterised by hyper-sexuality, visual agnosia, bulimia, placidity, hyperorality and memory deficits caused by lesions to the amygdala. The amygdala lesions can be due to many causes, including traumatic brain injury, systemic conditions and infections such as tuberculosis. Here, we present a case of partial KBS in a patient undergoing treatment for TBM.